The role of government fiscal and tax incentives in green technology innovation and enterprise development: implications for human health and hygiene - Shi, Yinghong; Ge, Jing (Frontiers in Public Health, 2025)
PurposeThis study aims to examine how government fiscal and tax incentives facilitate the development and application of green technologies, promoting corporate environmental responsibility and improving public health and hygiene.MethodsThe study utilizes empirical data from listed enterprises in the new energy automobile industry between 2018 and 2023. A multiple regression model is used to assess the effects of government subsidies and tax incentives on green technological innovation and enterprise growth, controlling for various factors such as enterprise size and R&D investment.ResultsThe analysis reveals that both government subsidies and tax incentives have a significant positive impact on green technology innovation and the development of green enterprises. The results also highlight regional variations, with enterprises in central and western regions benefiting more from tax incentives than those in eastern regions.ConclusionGovernment fiscal and tax incentives play a crucial role in fostering green technology innovation and sustainable enterprise development. To optimize the effectiveness of these policies, improvements in policy implementation, especially in addressing regional disparities, are necessary. This study provides insights for policymakers and green enterprises on leveraging incentives for long-term sustainability and public health benefits.